THE USE OF FTA CARD ON DNA SAMPLE PREPARATION FOR MOLECULAR OF PLANT DISEASE IDENTIFICATION - Purnamila Sulistyawati; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
Accurate and guick identification of pathogen is key to control the spread of plant disesases. Morphological identification is often ineffective because it requires fruit body which often are not presence, rely on characters which may be highly variable within and among species and can be slow and time consuming. Molecular identification of plant disease can overcome most of the shortcomings of morphological identification. Application of FTA Cardn for sample collection is crucial for the success of molecular identification of phatogen. The study present an earlier results on the suitability of FTA Card to collect sample in situ. The study was done on 4 different sample namely pure culture of fusarium sp., infected leaf, soil and seeds which assumed to have mycelium. The result indicate that FTA Card is effective as a collecting media of pathogen for most samples, paticularly for mycelium culture. Furthur experiments are still required to ensure the suitability of the card for leaf, seeds and soil samples.